Towards marine tourism management recommendations for the wrecks of HMS Erebus and HMS Terror National Historic Site, Nunavut, Canada - Potter, Stephanie Elizabeth (2020)
Over the last 25 years, climate change-induced increases in open water have led to a dramatic environmental and social transformation in the Canadian Arctic (Dawson, Pizzolato et al., 2018; Johnston, Viken et al., 2012). Increasing numbers of tourists aboard cruise ships and pleasure craft now venture farther into Canada’s Arctic waterways seeking unique natural and cultural experiences (Dawson et al., 2018; Johnston, Dawson, & Maher, 2017; Stewart & Draper, 2008; Stewart et al., 2007, 2019). While tourism growth presents important opportunities for the region, it is not void of challenges. This research examined marine tourism management concerns in relation to the recent discovery of the Franklin shipwrecks in shallow waters of the Northwest Passage. It is anticipated that the wrecks of HMS Erebus and HMS Terror will become a popular tourist attraction, leading to the need to explore context-specific management recommendations for the Wrecks of HMS Erebus and HMS Terror National Historic Site (WET NHS). This thesis used a systematic, three-staged data collection approach to examine: concerns related to marine and shipwreck tourism management; management “best” practices that have addressed similar concerns; and, expert feedback on the feasibility of applying these strategies to management of marine tourism at the WET NHS. Key management issues explored throughout included: which site(s) should be open to various visitor types; how tourism should use the sites; and, where and how visitor experience opportunities should be developed and managed. Based on the findings from the three-staged approach, ten context-specific management recommendations were made for the WET NHS, including: creating visitor guidelines, requiring local guides, developing anchoring restrictions, expanding the Inuit Guardian program, and offering high-quality visitor experiences on and off-site. Together, these recommendations helped inform recommendations for marine tourism management at the WET NHS for its protection and enjoyment by future generations, and the benefit of local Inuit communities.